2021
DOI: 10.1007/s00134-020-06331-9
|View full text |Cite
|
Sign up to set email alerts
|

Extracorporeal membrane oxygenation in patients with severe respiratory failure from COVID-19

Abstract: Purpose Limited data are available on venovenous extracorporeal membrane oxygenation (ECMO) in patients with severe hypoxemic respiratory failure from coronavirus disease 2019 (COVID-19). Methods We examined the clinical features and outcomes of 190 patients treated with ECMO within 14 days of ICU admission, using data from a multicenter cohort study of 5122 critically ill adults with COVID-19 admitted to 68 hospitals across the United States. To estimate the effect of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
223
5
10

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 176 publications
(252 citation statements)
references
References 40 publications
14
223
5
10
Order By: Relevance
“…Recent retrospective studies have reported that COVID-19 patients with ARDS supported by vv-ECMO overall have favorable outcomes [9][10][11]29 , with 63% of them being alive at 90 days in the ELSO registry 29 . However, the rate of severe bleeding, including intracranial haemorrhage, and fatal bleeding on ECMO was particularly high in these studies.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Recent retrospective studies have reported that COVID-19 patients with ARDS supported by vv-ECMO overall have favorable outcomes [9][10][11]29 , with 63% of them being alive at 90 days in the ELSO registry 29 . However, the rate of severe bleeding, including intracranial haemorrhage, and fatal bleeding on ECMO was particularly high in these studies.…”
Section: Discussionmentioning
confidence: 99%
“…From October 22, 2019 (8)(9)(10)(11)(12)(13)(14)(15)(16), respectively. The SOFA score tended to be higher in the COVID-19 group [12 (8.5-15.8) versus 9.5 (7.0-17.2) in the non-COVID-19 group).…”
Section: Patientsmentioning
confidence: 99%
See 2 more Smart Citations
“…In a very recent study on the outcome of VV-ECMO in COVID-19, the authors sought to estimate the effect of ECMO on mortality in comparison to conventional therapy. For this purpose, they analyzed data from 190 patients treated with ECMO among a cohort of 5122 critically ill COVID-19 patients in 68 US hospitals [171]. They performed a "target trial emulation", in which only mechanically ventilated patients with an age < 70 y, without malignancy, hospitalized in an ECMO center, and a PaO 2 /FiO 2 ratio < 100 mm Hg between day 1 and day 7, were included.…”
Section: Extracorporeal Membrane Oxygenation (Ecmo)mentioning
confidence: 99%